IMPROVING MATHEMATICS LEARNING OUTCOMES THROUGH PROBLEM BASED LEARNING (PBL) LEARNING MODEL FOR 4TH GRADE STUDENTS - Magdalena, Ina; Fadhillahwati, Nur Fauziah; Amalia, Rizki; Farhana, Syarifah (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
Problem-Based Learning (PBL) is an active learning approach that engages students in solving real-world problems to enhance their mathematics learning outcomes. This study aims to investigate the effectiveness of the PBL model in improving students' understanding and achievement in mathematics. The research employed an experimental design with a pretest-posttest control group. The participants were divided into an experimental group receiving PBL-based teaching and a control group receiving conventional teaching. The results demonstrated that students in the PBL group exhibited significantly better mathematics learning outcomes compared to the control group. These findings suggest that PBL holds promise as an effective learning approach, promoting critical thinking, problem-solving skills, collaboration, and motivation in mathematics. This study's implications may contribute to the development of learning strategies that emphasize the practical application of mathematical concepts, fostering students' deeper understanding and ability to apply these concepts effectively.